The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/15384101.2016.1242537
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-induced aberrant mitosis and mitotic slippage efficiently lead to proliferative death irrespective of canonical apoptosis and p53

Abstract: Spindle poisons elicit various cellular responses following metaphase arrest, but how they relate to longterm clonogenicity has remained unclear. We prepared several HeLa lines in which the canonical apoptosis pathway was attenuated, and compared their acute responses to paclitaxel, as well as long-term fate, with the parental line. Three-nanomolar paclitaxel induced brief metaphase arrest (<5 h) often followed by aberrant mitosis, and about 90% of the cells of each line had lost their clonogenicity after 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…However, in Taxol, MCF-7 cells predominantly underwent apoptosis, whereas MDA-MB-231 cells were prone to slippage (Supplementary Fig. S3D ), with inter- and intra-line variation consistent with previous studies 2 , 44 . We chose MCF-7 cells for generating a VDAC2 ko as these predominantly underwent death in mitosis.…”
Section: Resultssupporting
confidence: 89%
“…However, in Taxol, MCF-7 cells predominantly underwent apoptosis, whereas MDA-MB-231 cells were prone to slippage (Supplementary Fig. S3D ), with inter- and intra-line variation consistent with previous studies 2 , 44 . We chose MCF-7 cells for generating a VDAC2 ko as these predominantly underwent death in mitosis.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, in cells harboring high loads of chromosomal instability due to excess DNA mutations, induction of mitotic slippage has been proposed as a mechanism to kill these cells. Chemicals that inhibit the SAC, such as TTKi’s [ 294 – 296 ] and M2I-1 [ 58 , 62 ], have been shown to block CDC20 sequestration by the MCC, leading to activation of the APC and effective cancer cell death. It is proposed that premature activation of the APC pushes cells with high loads of chromosome instability into mitotic division before there is time to repair the damage, causing mitotic catastrophe [ 31 ].…”
Section: Contribution Of Apc Defects To a Dysregulated Cell Cyclementioning
confidence: 99%
“…Tumor chemotherapy is an important part of the comprehensive treatment for solid tumors (1). Paclitaxel, vincristine and other spindle poisons are widely used as first-line chemotherapy for various types of malignant tumor, such as breast cancer, cervical cancer and melanoma (2,3). One of the important methods in treating cancer is inducing tumor cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The latter two phenomena are the root cause of uncontrollable tumors and recurrence. Previous studies demonstrated that spindle poisons play a role in the induction of apoptosis in some cells (2,7). However, certain cells do not undergo apoptosis when exposed to such drugs, and instead form polyploids.…”
Section: Introductionmentioning
confidence: 99%